When Humble Leadership Works: The Roles of Perceived Team Engagement and Organizational Culture in Work Success - Arsadi; Ujang Fauzi; Andrean Eko Haryoko; Egi Andiyana (STIE Amkop Makassar, 2026)
known about its association with multidimensional work success and whether organizational culture strengthens its benefits. Integrating job demands–resources theory with a contextual perspective on organizational culture, this study tests five hypotheses linking humble leadership, perceived team engagement, work success, and two culture-based interaction effects. Cross-sectional survey data from a hierarchical public-sector work setting were analyzed using partial least squares structural equation modeling. The measurement model demonstrated satisfactory reliability, internal consistency, convergent validity, and discriminant validity. Humble leadership was positively related to perceived team engagement and work success, and perceived team engagement was positively related to work success. Organizational culture strengthened both the humble leadership–engagement and humble leadership–work success relationships, although its main associations with both outcomes were not significant. The model explained 43.1% of perceived team engagement variance and 66.6% of work success variance. These findings position humility as a context-dependent social resource whose benefits are stronger when culture supports involvement, consistency, adaptability, and mission. The study shows that organizational culture may function primarily as an enabling condition and offers implications for leadership development and supportive organizational systems.